Knowledge on Child Protection among Children: A Study on Selected Schools in Munali Constituency of Lusaka, Zambia - , Ui Munyima; , Aurick Mubita; , Moonga H. Mumba; , Brivery Siamabele; , Vincent Kanyamuna (Archives of Current Research International, 2025)
Child abuse remains a significant problem affecting children globally, manifesting in various forms such as sexual, physical, emotional, and psychological abuse. Many children also face forced labor, prostitution, abduction, and trafficking. Motivated by the prevalence and persistence of these issues, this study focused on two key objectives: to examine the knowledge children in Munali Constituency have on child protection and to explore the sources of this knowledge. A mixed-methods approach was employed, combining quantitative and qualitative methods (QUAL+quant). The study involved 328 pupils selected through systematic random sampling and four key informants purposively chosen. Data were collected using questionnaires, Key informant interviews and three focus group discussions. Quantitative data were analysed using the Statistical Package for Social Sciences (SPSS) and Excel, while qualitative data were analysed thematically. The findings revealed that children primarily received their knowledge of child protection from schools. However, this knowledge was largely inadequate to provide a clear understanding of child protection. Many children had limited knowledge of what child protection meant, including who to report abuse to, where to seek safety, and how to protect themselves from harm. The study concluded that children lack comprehensive knowledge of child protection and access to practical resources for reporting and addressing abuse. It recommended the need for more extensive and practical education on child protection, delivered through diverse sources, to ensure children are empowered to recognize, respond to, and prevent abuse effectively. The study faced limitations due to the vulnerability of children, as discussions about child protection could evoke emotional distress, especially for those with prior trauma. To mitigate this, researchers avoided intrusive questions and ensured a safe, supportive environment to promote participants' comfort.